Self-Selection Bias in the Evolution of Voluntary Energy Conservation Programs - Hartman, Raymon S. (The Review of Economics and Statistics, 1988)
While voluntary energy conservation programs have been extensively promoted by electric utilities and public utility commissions, their effectiveness has been insufficiently critiqued. This paper contributes to the growing evaluation of such programs by measuring the net energy savings directly attributable to an actual set of programs. The analysis explicitly corrects for the self-selection bias that can arise in program evaluation. The correction is found to be important; traditional evaluation methods are subject to considerable bias. Correcting for this bias, the amount of program-induced energy savings is found to be considerably less than traditionally believed. Copyright 1988 by MIT Press.